Pregabalin beneficial effects on sleep quality or health-related quality of life are poorly correlated with reduction on pain intensity after an eight-week treatment course - Pérez Lloret, Santiago (2012)
Fil: Pérez Lloret, Santiago. Paul Sabatier University. Pharmacology Department; Francia